2022
DOI: 10.1002/dad2.12299
|View full text |Cite
|
Sign up to set email alerts
|

A novel computer adaptive word list memory test optimized for remote assessment: Psychometric properties and associations with neurodegenerative biomarkers in older women without dementia

Abstract: Introduction This study established the psychometric properties and preliminary validity of the Stricker Learning Span (SLS), a novel computer adaptive word list memory test designed for remote assessment and optimized for smartphone use. Methods Women enrolled in the Mayo Clinic Specialized Center of Research Excellence (SCORE) were recruited via e‐mail or phone to complete two remote cognitive testing sessions. Convergent validity was assessed through correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Results of correlation analyses align with this intent and support our hypothesis that the SLS and AVLT would show a significant correlation (r = 0.62 observed), and therefore further support convergent validity (Aim 3). Our initial pilot study similarly supported the convergent validity of the SLS, but slightly lower correlation coefficients were observed in that study, likely due to homogeneity of that sample (e.g., all female, restricted age range, excluded individuals with dementia), and potentially due to a longer duration between in-person and remote testing (average 10 months) 13 . The current results are particularly notable given that an exact computerized replication of the AVLT facilitated by audio recording and speech recognition to allow self-administered on an iPad showed only slightly higher correlations (r=0.63-0.70) with the AVLT as typically administered in a well-controlled cross-over design completed in a clinic setting 43 .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Results of correlation analyses align with this intent and support our hypothesis that the SLS and AVLT would show a significant correlation (r = 0.62 observed), and therefore further support convergent validity (Aim 3). Our initial pilot study similarly supported the convergent validity of the SLS, but slightly lower correlation coefficients were observed in that study, likely due to homogeneity of that sample (e.g., all female, restricted age range, excluded individuals with dementia), and potentially due to a longer duration between in-person and remote testing (average 10 months) 13 . The current results are particularly notable given that an exact computerized replication of the AVLT facilitated by audio recording and speech recognition to allow self-administered on an iPad showed only slightly higher correlations (r=0.63-0.70) with the AVLT as typically administered in a well-controlled cross-over design completed in a clinic setting 43 .…”
Section: Discussionsupporting
confidence: 54%
“…Preliminary support for the feasibility, reliability and validity of the SLS was previously reported in an all-female older adult sample 13 . Whereas that prior study used traditional approaches to test validation, the current study aimed to establish test validity using a novel approach to avoid the inherent issues with existing validation approaches.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…To investigate whether the outcomes of remote and unsupervised digital cognitive assessments are comparable to traditional cognitive measures, construct validity was determined. This is usually accomplished by comparing novel measures against conventional cognitive tests used in controlled studies ( 14 , 19 , 21 , 48 50 ). Our results showed that, as expected, the correlation between mobile app-based memory tasks and individual conventional cognitive measures was strongest for episodic memory measures, indicating convergent validity.…”
Section: Discussionmentioning
confidence: 99%
“…All tests were twotailed, and a p-value <0.05 was considered statistically significant. All statistical analyses were performed using R Statistical Software (version R 4.1.2) (47). Recruitment for the study is ongoing.…”
Section: Statistical Analysesmentioning
confidence: 99%